2001
DOI: 10.1016/s0735-1097(01)01253-0
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency endovascular gene delivery via therapeutic ultrasound

Abstract: Endovascular US enhanced vascular gene delivery and increased the efficiency of nonviral platforms to levels previously attained only by adenoviral strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…Secondly, the sonication needed to achieve enhanced gene expression by either plasmid alone or coupled to MSP is within the range emitted by diagnostic transducers. [107][108][109] Thus, if efficient gene transfer could be achieved by this technique, it would have great advantages in clinical use over other physical methods, such as electroporation. Thirdly, enhanced transgene expression can be achieved by US alone or in combination with other non-viral delivery systems, such as lipoplex-mediated gene delivery.…”
Section: Microbubbles and Ultrasoundmentioning
confidence: 99%
“…Secondly, the sonication needed to achieve enhanced gene expression by either plasmid alone or coupled to MSP is within the range emitted by diagnostic transducers. [107][108][109] Thus, if efficient gene transfer could be achieved by this technique, it would have great advantages in clinical use over other physical methods, such as electroporation. Thirdly, enhanced transgene expression can be achieved by US alone or in combination with other non-viral delivery systems, such as lipoplex-mediated gene delivery.…”
Section: Microbubbles and Ultrasoundmentioning
confidence: 99%
“…Indeed, enhancement of gene expression was observed by irradiating ultrasonic wave to the tissue after injection of DNA. 20,21 Since ultrasound application is flexible and safe, its use in gene delivery has a great advantage in clinical use. Recently, it was reported that combination of microbubble with ultrasound could further increase the gene expression level.…”
Section: Introductionmentioning
confidence: 99%
“…Since the sonication power needed for achieving enhanced gene expression is within safe therapeutic and imaging limits, 13,16,17 this method might be combined with ultrasound imaging of a target tissue. This would give it an advantage over other methods, such as electroporation, for which clinically safe limits have yet to be established.…”
Section: Introductionmentioning
confidence: 99%